Photochemistry and spectroscopy of a five-chlorophyll reaction center of photosystem II isolated by using a Cu affinity column. - Vacha, F (1995)
A reaction center of photosystem II was isolated from Pisum sativum by using immobilized metal affinity chromatography. This reaction center is photochemically active and has a room temperature Qgamma chlorophyll (Chl) absorption band peaking at 677.5 nm. From HPLC analysis, the pigment stoichiometry was suggested to be 5 Chls per 1 beta-carotene per 2 pheophytins. Low-temperature absorption measurements at 77 K were consistent with the removal of one of the Chls associated with the usual form of the reaction center isolated by using ion-exchange chromatography. Transient absorption spectroscopy on the picosecond time scale indicated that the Chl removed belongs to a pool of Chl absorbing at approximately 670 nm (C670II) that transfers energy relatively slowly to the primary donor P680 in support of our recently proposed model. The results also support the previous conclusion that radical pair formation is largely associated with a 21-ps time constant when P680 is directly excited and that the identity of C670II is likely to be peripherally bound Chls possibly ligated to conserved His residues at positions 118 on the D1 and D2 proteins.